THE TRAJECTORY OF URBAN GROWTH, LAND USE PATTERNS, AND MOBILITY IN KANO URBAN AREA, NIGERIA - Solomon Dyachia Zakka; Amos Danladi; Haruna Ahmadu (American Journals Publishing, 2022)
The trajectory of urban Growth, Land use patterns, and mobility in Kano Nigeria was motivated by the trend of rapid urbanization in third world countries of sub-Saharan Africa that is driven by demography and forces of push-pull factors. The study aimed to examine the trend of urban growth, Land use patterns, and urban mobility, in the sub-Saharan city of Kano, and to ascertain the implications and consequences of this trend on the city transitional process on the city sustainability index. Method of Remote Sensing and Geographic Information System (RS/GIS) was used to extract imageries maps for Kano Urban Area. Spatial analysis of data was carried out using the ArcGIS 10.2 software. Furthermore, a set of questionnaires were administered. Respondents were drawn from the sample of urban commuters with n=600. Collected data were analysed using frequency analysis. Findings from the research revealed the growth of the city is characterised by the following: steady expansion of the built-up area by 346.15% over the past thirty (30) years, the gradual fragmentation of the urban landscape is supported by a spatial metric indicator of an increase in urban landscape patches from 63 in the year 1990 to 115 patches in the year 2020.   An average Fractal Dimension Index (FD) value of approximately = 1 was calculated. The research further confirmed the transformation of the city from mono-centric form to polycentric form by creating a sphere of influence and attraction for the City of Kano. A total of 81.83% of all commuter trips are attracted to the various poles of attraction located within the city sphere of influence and attraction. The research has revealed high dependence on tricycles as the common mode of transportation for the city. This has resulted in excessive traffic congestion and an increase in traffic time for urban commuters. The repositioning of the land administration system to guide urban growth and the land-use patterns toward the classical polycentric model, the provision of light rail transit to connect the various poles of attraction within the city sphere of influence, and the entrenchment of a mass transit road transport system to reduce traffic congestion were some of the policy approach measures suggested for the city.
Keywords: Urban Growth; Planning; Land use